2014
DOI: 10.1590/s1415-47572014000400011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Jatropha curcas JcR1MYB1 gene encoding a putative R1-MYB transcription factor

Abstract: The cDNA encoding the R1-MYB transcription factor, designated as JcR1MYB1, was isolated from Jatropha curcas using rapid amplification of cDNA ends. JcR1MYB1 contains a 951 bp open reading frame that encodes 316 amino acids. The deduced JcR1MYB1 protein was predicted to possess the conserved, 56-amino acid-long DNA-binding domain, which consists of a single helix-turn-helix module and usually occurs in R1-MYBs. JcR1MYB1 is a member of the R1-MYB transcription factor subfamily. A subcellular localization study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this study, we identified a MYB transcription factor, RhMYB108, as being involved in the interplay between ethylene and JA signaling and thus regulating petal senescence in rose. According to their number of conserved MYB structural motifs, MYB proteins are classified into R1-MYB, R2R3-MYB, R3-MYB, and R4-MYB subfamilies 27,28 and function in the regulation of plant growth, hormone signal transduction, stress and disease resistance, and secondary metabolism [29][30][31][32][33] . Here, we show that RhMYB108, which belongs to the R2R3-MYB family, is intensely expressed in rose petals.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified a MYB transcription factor, RhMYB108, as being involved in the interplay between ethylene and JA signaling and thus regulating petal senescence in rose. According to their number of conserved MYB structural motifs, MYB proteins are classified into R1-MYB, R2R3-MYB, R3-MYB, and R4-MYB subfamilies 27,28 and function in the regulation of plant growth, hormone signal transduction, stress and disease resistance, and secondary metabolism [29][30][31][32][33] . Here, we show that RhMYB108, which belongs to the R2R3-MYB family, is intensely expressed in rose petals.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of MYB transcription factors is their nuclear localization signal peptides [24][25][26] . The rice gene OsMYB511 is expressed specifically in the nucleus 24 , as are the Jatropha curcas gene JcR1MYB1 25 and the Nicotiana benthamiana gene NbPHAN 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The other name of the plant is Curcas purgans. Pharmacological reports revealed that it is having anti microbial 4,5,6 , anti-inflammatory 7 , antimetastatic 8 , antitumor 8 , coagulant and anti-coagulant (dose dependent), disinfectant, antiparasitic activity.…”
mentioning
confidence: 99%